2012
DOI: 10.1088/0953-2048/25/8/084021
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Te–Se epitaxial thin films with enhanced superconducting properties

Abstract: Epitaxial Fe–Te–Se thin films were deposited by pulsed laser deposition at 250–600 °C on SrTiO3 (100), MgO (100), LaAlO3 (100) and CaF2 (100) single crystal substrates. The best superconducting film was grown on CaF2:  K and  K with Tdep = 300 °C and 3 Hz. Critical current density Jc (T = 4.2 K) was 0.41 × 106 A cm−2 at 0 T and 0.23 × 106 A cm−2 at 9 T. The angular dependence of Jc shows a broad c-axis correlated peak when B ≥ 3 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 29 publications
8
47
0
1
Order By: Relevance
“…Furthermore, films on SrTiO 3 show a peak in the angular dependence of J c for H || c [11][12][13]. Similar c-axis peaks in J c (θ) have been observed for films deposited on CaF 2 substrate [14]. However, no additional peaks have been observed in FeSe 0.5 Te 0.5 films on LAO [11] and Fe-buffered MgO substrates [15][16].…”
Section: Introductionsupporting
confidence: 65%
“…Furthermore, films on SrTiO 3 show a peak in the angular dependence of J c for H || c [11][12][13]. Similar c-axis peaks in J c (θ) have been observed for films deposited on CaF 2 substrate [14]. However, no additional peaks have been observed in FeSe 0.5 Te 0.5 films on LAO [11] and Fe-buffered MgO substrates [15][16].…”
Section: Introductionsupporting
confidence: 65%
“…They state that the key to high-quality 11 thin films is the absence of interfacial reactions between the FeTeSe film and the substrate (figure 7). Mele et al [15] and Bellingeri et al [16,[39][40][41] confirmed that smooth, cube-on-cube epitaxial FeTe 0.5 Se 0.5 films can be obtained on several substrates: MgO, LAO, STO, yttria-stabilized zirconia (YSZ), MgO, CaF 2 and LiF. Iida et al [14] reported for the first • to the MgO substrate, whereas the FeTeSe film showed the cube-on-cube epitaxial relation (figure 8).…”
Section: Fet E X Se 1−x Filmsmentioning
confidence: 84%
“…Mele et al [15] systematically analyzed the dependence of T c of FeTeSe/CaF 2 films on the experimental parameters, exploring a wide range of deposition temperatures (from 250 to 450…”
Section: Effect Of Deposition Temperature and Number And Frequency Ofmentioning
confidence: 99%
See 2 more Smart Citations